The role of growth options in explaining stock returns - Trigeorgis, Lenos; Lambertides, Neophytos (My University, 2014)
We extend the Fama-French (1992) model by considering growth option (as well as distress/leverage) variables in explaining the cross section of stock returns. We find that growth option variables, namely growth in capital investment and yet-unexercised growth options (GO), are significantly and negatively related to stock returns. Investors may be willing to accept lower average returns from growth stocks in exchange for a more favorable (positively skewed) risk-return profile. Book-to-market (BM) ratio seems to proxy for omitted distress/leverage variables. When these are explicitly accounted for, BMis not that significant. Our growth options variables have added explanatory power.
Keywords: Asset pricing; Book-to-market; Growth options; Stock returns; Value-size effects